Sites occupancy preference of Bi3+ and white light emission through co‐doped Sm3+ in LiGd5P2O8. Issue 8 (5th March 2018) - Xu, Hongwei; Wang, Lili; Tan, Lingling; Wang, Deguo; Wang, Chunyu; Shi, Jinsheng
Abstract: Bi 3+, Sm 3+ ‐activated LiGd5 P2 O8 (LGPO) phosphors were prepared through high‐temperature solid‐state method. In LGPO host, there are 5 types of Gd crystallographic sites, named as Gd(1)/Gd(2)/Gd(3)/Gd(4), and Gd(5). Bi 3+ ‐activated LGPO phosphors exhibit 1 broad excitation band from 250 to 320 nm centered at 293 nm and a broad asymmetric emission band ranging from 350 to 600 nm with the maximum value approximately at 409 nm. It can be concluded from dual‐emission spectra that Bi 3+ may occupy 2 Gd sites and an obvious spectral blue‐shift appeared with increasing Bi 3+ content, which is caused by the intensity of crystal field of Bi 3+ is decreased. Notably, through the calculation of each Gd‐O chemical parameter, the environmental factor ( h e ) value of each Gd site can be obtained and it can be further inferred that 2 emission bands centered at 409/461 nm are ascribed to Bi 3+ ions which occupies Gd(3) and Gd(4) sites, respectively. Energy transfer from Bi 3+ to Sm 3+ ions in Bi 3+ /Sm 3+ co‐doped LGPO samples occurred and it realizes the color‐tunable emission from cyan to yellow including white‐light emission, through controlling Sm 3+ content. Moreover, energy transfer mechanism between Bi 3+ and Sm 3+ ions is verified to be dipole‐dipole interaction by analyzing the spectroscopic experimental results and the critical distance between them is calculated to be 8.22 Å by concentration quenching method. Finally, it is illustrated that Bi 3+ and Sm 3+ co‐doped LGPO phosphors will be a promising candidate for n‐UV chip pumped w‐LEDs.